2011
DOI: 10.1002/tie.20416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a local host on the success of an international assignment

Abstract: This longitudinal study examined whether contact with a local host in the Netherlands positively impacts on the adjustment and performance of “Western” expatriates with English or French as their first language. Thirty‐one expatriates were put in contact with a Dutch host with whom they would have regular contact over nine months; another 30 similar expatriates would have no contact with a host. After a five‐month period of contact with a host, there was a positive impact on interaction adjustment. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…To foster the integration of foreign talent into the environment and team, one recommendation would be to establish a buddy system, by pairing a local player with a foreign one. Such a system has shown to provide benefits to expatriates in terms of adjustment and intercultural competence (Van Bakel, Gerritsen, & Van Oudenhoven, , ). Equally, it could be a possibility to identify host families within the reach of the club community to host foreign players and introduce them to the local language and culture for a few weeks—as happened to Marissa K.—before finding appropriate individual housing.…”
Section: Discussionmentioning
confidence: 99%
“…To foster the integration of foreign talent into the environment and team, one recommendation would be to establish a buddy system, by pairing a local player with a foreign one. Such a system has shown to provide benefits to expatriates in terms of adjustment and intercultural competence (Van Bakel, Gerritsen, & Van Oudenhoven, , ). Equally, it could be a possibility to identify host families within the reach of the club community to host foreign players and introduce them to the local language and culture for a few weeks—as happened to Marissa K.—before finding appropriate individual housing.…”
Section: Discussionmentioning
confidence: 99%
“…As they embark on their new assignments, expatriates are often forced to leave behind a social support network (van Bakel, Gerritsen, & van Oudenhoven, 2011), that could be relied upon as and when needed. Instead they must now attempt 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60…”
Section: Importance Of Role Information and Social Supportmentioning
confidence: 99%
“…The role of contact quality was examined for each of the dependent variables in the three previously mentioned studies (Psychological Health, Satisfaction with Life, Physical Health, Sociocultural Adjustment, General Adjustment, Interaction Adjustment, Work Adjustment, Open‐Mindedness, Social Initiative, Cultural Empathy, Flexibility, Host National Access, Host National Social Support, Assess Your Own Performance, Most Recent Actual Performance Evaluation, and Desire to Terminate the Assignment; see Van Bakel et al, , , ), yet contact quality played a role for only four of these variables. These are reported in this article (Interaction Adjustment, Open‐Mindedness, Social Initiative, and Host National Social Support).…”
Section: Instrumentsmentioning
confidence: 99%
“…For example, the Expat Explorer Survey (HSBC, ) showed that Europe, and especially the Netherlands, was the most difficult region in which to make local friends. One solution is to purposely put expatriates in touch with a local host (Van Bakel, Gerritsen, & Van Oudenhoven, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation